Sexual Dimorphism in Kisspeptin Signaling - Eun Bee Lee; Iman Dilower; Courtney A. Marsh; Michael W. Wolfe; Saeed Masumi; Sameer Upadhyaya; Mohammad A. Karim Rumi (Cells, 2022)
Kisspeptin (KP) and kisspeptin receptor (KPR) are essential for the onset of puberty, development of gonads, and maintenance of gonadal function in both males and females. Hypothalamic KPs and KPR display a high degree of sexual dimorphism in expression and function. KPs act on KPR in gonadotropin releasing hormone (GnRH) neurons and induce distinct patterns of GnRH secretion in males and females. GnRH acts on the anterior pituitary to secrete gonadotropins, which are required for steroidogenesis and gametogenesis in testes and ovaries. Gonadal steroid hormones in turn regulate the KP neurons. Gonadal hormones inhibit the KP neurons within the arcuate nucleus and generate pulsatile GnRH mediated gonadotropin (GPN) secretion in both sexes. However, the numbers of KP neurons in the anteroventral periventricular nucleus and preoptic area are greater in females, which release a large amount of KPs in response to a high estrogen level and induce the preovulatory GPN surge. In addition to the hypothalamus, KPs and KPR are also expressed in various extrahypothalamic tissues including the liver, pancreas, fat, and gonads. There is a remarkable difference in circulating KP levels between males and females. An increased level of KPs in females can be linked to increased numbers of KP neurons in female hypothalamus and more KP production in the ovaries and adipose tissues. Although the sexually dimorphic features are well characterized for hypothalamic KPs, very little is known about the extrahypothalamic KPs. This review article summarizes current knowledge regarding the sexual dimorphism in hypothalamic as well as extrahypothalamic KP and KPR system in primates and rodents.